2016
DOI: 10.1038/jhh.2016.53
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sodium and nocturnal blood pressure dipping in normotensive men and women

Abstract: Impaired nocturnal blood pressure (BP) dipping (i.e., <10% decline in nocturnal BP) is associated with an increased risk of cerebrovascular and cardiovascular diseases. Excess sodium has been shown to impair BP regulation and increase cardiovascular disease risk, yet few studies have assessed the influence of dietary sodium on nocturnal dipping in normotensive adults. The purpose of this study was to determine the effects of dietary sodium on BP dipping in normotensive men and women. Eighty healthy normotensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The outcomes examined were diverse: Six studies assessed mortality outcomes, four studies assessed morbidity outcomes, three studies assessed outcomes related to symptoms/quality of life/functional status, studies assessed BP outcomes; eight studies assessed other clinically relevant surrogate outcomes; and nine studies assessed physiologic outcomes (Table ) . A range of outcomes were captured by the studies considered lower quality, including all‐cause mortality, gastric cancer, end‐stage renal disease requiring dialysis or transplant, cardiovascular events, hypertension prevalence, headaches/migraines, quality of life, multiple sclerosis, BP, cognitive function, osteoporosis risk and prevalence, nonalcoholic fatty liver disease, type 2 diabetes, carotid atherosclerosis, bone mineral density, changes in left ventricular mass, inflammatory markers, albuminuria, and other urinary markers . Most of these studies (n = 40) found adverse effects of dietary salt on health outcomes and benefits of a sodium‐restricted diet on health, except for 7 that were neutral and one reported worsening symptoms with a sodium‐restricted diet in the elderly …”
Section: Resultsmentioning
confidence: 99%
“…The outcomes examined were diverse: Six studies assessed mortality outcomes, four studies assessed morbidity outcomes, three studies assessed outcomes related to symptoms/quality of life/functional status, studies assessed BP outcomes; eight studies assessed other clinically relevant surrogate outcomes; and nine studies assessed physiologic outcomes (Table ) . A range of outcomes were captured by the studies considered lower quality, including all‐cause mortality, gastric cancer, end‐stage renal disease requiring dialysis or transplant, cardiovascular events, hypertension prevalence, headaches/migraines, quality of life, multiple sclerosis, BP, cognitive function, osteoporosis risk and prevalence, nonalcoholic fatty liver disease, type 2 diabetes, carotid atherosclerosis, bone mineral density, changes in left ventricular mass, inflammatory markers, albuminuria, and other urinary markers . Most of these studies (n = 40) found adverse effects of dietary salt on health outcomes and benefits of a sodium‐restricted diet on health, except for 7 that were neutral and one reported worsening symptoms with a sodium‐restricted diet in the elderly …”
Section: Resultsmentioning
confidence: 99%
“…Another potential issue in comparison of different study results is the BP measurement. While most studies still use the conventional measurements, from the studies that employ 24-h BP measurements only a limited number is investigating salt sensitivity solely in healthy, normotensive populations (48)(49)(50) .…”
Section: Genetics Of the Blood Pressure Response To Sodium Loading Smentioning
confidence: 99%
“…The SS assessment protocol has been explained elsewhere (Brian et al, 2017; Matthews et al, 2015). In brief, participants completed a run-in week of recommended dietary sodium intake (100 mmol•day −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The change in 24hr MAP from low to high sodium was used as a continuous measurement variable for SS (de Leeuw and Kroon, 2013). Twenty-four hour urinary excretion of sodium was used to confirm participant compliance to the SS test diet and has been published elsewhere (Brian et al, 2017). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation